2020
DOI: 10.1021/acs.biomac.9b01694
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sugars on the Real-Time Adsorption of Expansin on Cellulose

Abstract: Biological pretreatment is a safe and environmentally friendly method for disrupting recalcitrant ligno­cellulose structures. Expansin and expansin-like proteins are used to open up the cellulose structure and display significant synergism when mixed with cellulases that catalyze the breakdown of (hemi)­cellulose into sugars. However, the adsorption behavior of expansin in the presence of sugar products is yet unknown. In this work, we monitored the effects of various sugars on the real-time adsorption of Baci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Other investigations of EXLX1 adsorption onto cellulose, using quartz crystal microbalance with dissipation (QCM-D), confirmed that cellobiose and xylose enhanced EXLX1 adsorption at low concentrations but inhibited it at high concentrations (Zhang et al, 2020 ). Monitoring real-time adsorption of endo/exo-glucanases with EXLX1 and the enzymatic hydrolysis of cellulose showed synergistic effects.…”
Section: Expansin Structure and Mode Of Actionmentioning
confidence: 89%
“…Other investigations of EXLX1 adsorption onto cellulose, using quartz crystal microbalance with dissipation (QCM-D), confirmed that cellobiose and xylose enhanced EXLX1 adsorption at low concentrations but inhibited it at high concentrations (Zhang et al, 2020 ). Monitoring real-time adsorption of endo/exo-glucanases with EXLX1 and the enzymatic hydrolysis of cellulose showed synergistic effects.…”
Section: Expansin Structure and Mode Of Actionmentioning
confidence: 89%
“…They further carried out real-time QCM-D monitoring of expansin adsorption during the enzymatic hydrolysis of lignocellulose in biorefineries. These studies provide useful insights on highly efficient lignocellulose conversion. …”
Section: An Overview Of Biomacromolecular Characterizations Using Qcm-dmentioning
confidence: 99%
“…Overall, BsEXLX1 exhibited a high binding ability on lignin with the maximum adsorption of 260−283 ng cm −2 , which is much higher than that on cellulose (120−160 ng cm −2 ) as measured in our previous study. 18,19 During the experiment, ΔD showed an opposite tendency with the frequency, i.e., it increased to a maximum value before decreasing. In the initial stage, the dissipation value increased rapidly due to the adsorption of BsEXLX1, making the film more viscoelastic.…”
Section: ■ Introductionmentioning
confidence: 97%
“…Considering the binding ability of expansin, an understanding of the expansin adsorption will greatly contribute to the understanding of the action mechanism. Current research on expansin adsorption mainly concentrates on the adsorption site, adsorbed amount after equilibrium, and real-time adsorption behavior on cellulose. , For example, we recently found that cellobiose and xylose can improve the adsorption of Bs EXLX1 on cellulose at low concentrations but disrupt adsorption at high concentrations . However, the adsorption of expansin on lignin is unknown and remains one of the important unanswered questions in the field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation